A Bibliometric Analysis on Fuel Prices Fluctuations and Tourism under the Era of Sustainable Development - Awan, Ayesha; Bibi, Mehwish; Bano, Friha; Shoukat, Sana (Pakistan Journal of Humanities and Social Sciences, 2023)
The tourism industry has great potential for growth in any economy. Its excessive input-to-output ratio has a significant favorable effect on the economy. Oil costs are affecting the tourism industry because oil fuel prices are a direct factor influencing the tourist industry both demand and supply. There has been demonstrated how the price of petroleum has affected transportation, aviation, and tourism has varied. So, for this purpose, the paper uses a bibliometric analysis method based on Scopus statistics, along with R studio productive methods and Vos viewer for visual results to determine the current trends within the along with oil price's consequence on the tourist industry. The findings used Descriptive analyses, thematic maps, and current trends of issues like oil price shocks and tourism operations to predict the frequency of courses. Lastly, by offering new research directions in sustainable tourism, this bibliometric analysis helps us to draw a conclusion to study.